Psychosocial functioning is correlated with activation in the anterior cingulate cortex and left lateral prefrontal cortex during a verbal fluency task in euthymic bipolar disorder: A preliminary fMRI study. Issue 3 (1st November 2013) - Yoshimura, Yasushi; Okamoto, Yasumasa; Onoda, Keiichi; Okada, Go; Toki, Shigeru; Yoshino, Atsuo; Yamashita, Hidehisa; Yamawaki, Shigeto
<x xml:space="preserve">Abstract</x> Aim Cognitive impairment may account for functional and occupational disability in patients with bipolar disorder even during periods of euthymia. While imaging suggests structural, neurochemical, and functional abnormalities in bipolar disorder patients, the pathophysiology of these deficits has not been elucidated. It was hypothesized that euthymic bipolar patients would have different cortical activation during a verbal fluency task compared to healthy controls, and that psychosocial functioning would be associated with prefrontal cortical activation during the task in the bipolar group. Methods Ten euthymic bipolar patients and 10 healthy control participants (matched for age, gender, and years of education) underwent functional magnetic resonance imaging (fMRI) during a verbal fluency task, tapping task and visual task. Correlational analysis between the fMRI brain activation and clinical variables of the participants, including Global Assessment of Functioning (GAF) score, was performed. Results Compared to the controls, euthymic bipolar patients had significantly greater activation in the bilateral precuneus with similar behavioral performance during the verbal fluency task. There were no significant differences between the groups for the visual task or the simple motor task. Activation in both the left anterior cingulate cortex (ACC) and the left dorsolateral prefrontal cortex (PFC) were significantly positively correlated with GAF score in the euthymic bipolar patients. Conclusion Both the ACC and lateral PFC regions are components of a neural network that plays a critical role in psychosocial functioning, and are often found to be affected in bipolar patients.